Layered double hydroxides as electrode materials for flexible energy storage devices. (1st April 2023) - Lin, Qifeng; Wang, Lili
Abstract: To prevent and mitigate environmental degradation, high-performance and cost-effective electrochemical flexible energy storage systems need to be urgently developed. This demand has led to an increase in research on electrode materials for high-capacity flexible supercapacitors and secondary batteries, which have greatly aided the development of contemporary digital communications and electric vehicles. The use of layered double hydroxides (LDHs) as electrode materials has shown productive results over the last decade, owing to their easy production, versatile composition, low cost, and excellent physicochemical features. This review highlights the distinctive 2D sheet-like structures and electrochemical characteristics of LDH materials, as well as current developments in their fabrication strategies for expanding the application scope of LDHs as electrode materials for flexible supercapacitors and alkali metal (Li, Na, K) ion batteries.